1999
DOI: 10.1089/107999099312812
|View full text |Cite
|
Sign up to set email alerts
|

IFN-gamma Induction of p21WAF1 Is Required for Cell Cycle Inhibition and Suppression of Apoptosis

Abstract: Interferons (IFN) inhibit the growth of tumor cells by blocking the progression of their cell cycle. Recently, we showed that this cell cycle inhibition correlates with the ability of IFN to upregulate the cyclin-dependent kinase inhibitor p21(WAF1). This, however, is not proof of a causal relationship. Using p21(WAF1)-deficient cells derived from the HCT116 colon adenocarcinoma cell line, we now show that p21(WAF1) is indeed responsible for the antiproliferative effects of the type II IFN, IFN-gamma. IFN-gamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 24 publications
1
36
0
Order By: Relevance
“…IFNg inhibits cell proliferation via cell type-specific pathways that involve CKIs, such as p21Cip1 (29,30) and p27Kip1 (31,32). It has been shown that STAT1 interacts directly with cyclin D1/ Cdk4 and mediates the cell-cycle arrest of human U3A cells (33).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IFNg inhibits cell proliferation via cell type-specific pathways that involve CKIs, such as p21Cip1 (29,30) and p27Kip1 (31,32). It has been shown that STAT1 interacts directly with cyclin D1/ Cdk4 and mediates the cell-cycle arrest of human U3A cells (33).…”
Section: Discussionmentioning
confidence: 99%
“…Mice transgenic for the pmel-1-TCR, which recognizes the H-2D b -restricted epitope EGSRNQDWL from gp100 (gp100 [25][26][27][28][29][30][31][32][33] ), were obtained from The Jackson Laboratory. All mice were housed in a pathogen-free environment, and all animal procedures were conducted in accordance with institutional guidelines.…”
Section: Mice Tumor Cells and Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the interferon inducible transcription factor IRF-1 has been shown to functionally synergise with p53 (Tanaka et al, 1996). However, IFNs, can regulate proliferation and death in cells that contain functionally inactive, or are absent in, p53 (Subramanium and Johnson, 1997) and addition of IFN-g to p53 null cells can still result in an increase in the levels of p21 waf1/Cip1 (Hobeika et al, 1999). Clearly the molecular pathways leading to IFN-mediated cell death and cell cycle arrest have not yet been completely de®ned.…”
Section: Discussionmentioning
confidence: 99%
“…IFN-␥ has been shown to up-regulate the cyclin-dependent kinase inhibitor p21 (WAF1). 29,30 The mechanisms of action are suggested to occur through signal transducers and activators of transcription protein-1, which can by activated by IFN-␥. 30 The up-regulation of p21 inhibits entry of cells into the S phase of the cell cycle, thereby causing cell growth arrest.…”
Section: Fujii Huang Fong Et Al: Intratumoral Ifn-␥ Retroviral Delmentioning
confidence: 99%